Web-Based Hospital Human Resource Management and Activity Information System (SIM-KARS): A Case Study at RSKM Regina Eye Center - Arsyad Hamidi; Ilham Tri Maulana; Nency Extise Putri; Yessy Prima Putri (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Information systems play a critical role in enhancing service quality and operational efficiency in healthcare institutions. However, personnel and activity management in many hospitals is still conducted through manual or fragmented processes, leading to data duplication, administrative delays, limited transparency, and difficulties in generating accurate reports. RSKM Regina Eye Center faces similar challenges, particularly in recording daily employee activities, managing leave and overtime submissions, and organizing doctor schedules, which are not yet integrated into a unified system. This study aims to design and develop a web-based Hospital Personnel and Activity Management Information System (SIM-KARS) to address these issues. The system was developed using the Waterfall method for software development and implemented with the Laravel framework, supported by PHP, JavaScript, and MySQL. System evaluation was conducted through black-box testing and a user satisfaction assessment. The results indicate that SIM-KARS improves administrative efficiency, data accuracy, transparency, and ease of access to personnel information. User evaluation results show a satisfaction level of 90%, reflecting positive user acceptance and perceived usefulness. This study contributes a practical, integrated model for digitalising personnel and operational activity management in specialised hospitals to support data-driven decision-making and sustainable healthcare administration. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-BeingSDG 9: Industry, Innovation, and InfrastructureSDG 16: Peace, Justice, and Strong Institutions